Impact of Seasonal Temperature Changes on Sesquiterpene Lactone and Sugar Concentrations in Hydroponically Grown Lettuce - Mason McLemore; Shivani Kathi; John Unterschuetz; Tyler Mason; Niels Maness; Donna Chrz; Bruce Dunn; Charles Fontanier; Bizhen Hu (HortScience)
Lettuce is one of the most important leafy vegetables in the United States, and it is subjected to a decrease in edible quality when cultivated in environments with hot temperatures and increased daylength. Specifically, bitter-tasting compounds called sesquiterpene lactones (SLs) accumulate in certain cultivars and lettuce market types, especially during the bolting stage. However, increased sugar accumulation may offset bitterness, with high sugar:SL ratios reducing the bitter flavor perception. Hence, it is important to determine the effect of seasonal temperatures on sugar, SL, and sugar:SL accumulation in lettuce cultivars to predict the likelihood of perceived bitterness. Twelve cultivars spread across four different commonly grown market types (i.e., Romaine, Butterhead, Batavian, and Salanova®) were grown for four harvest seasons (Spring 2020, Fall 2020, early Summer 2021, and Winter 2021) in nutrient flow technique hydroponic culture. Lettuces exhibited significant differences in harvest seasons, cultivar, and their interaction for free SLs and total SLs, sucrose, and sugar:SL ratio. Specifically, plant fresh weight and total SLs were greatest in Spring 2020 and Fall 2020, respectively, and lowest in Winter 2021. Total sugars were the same between harvests, and Winter 2021 had a significantly lower sugar:SL ratio than that of the other three harvests. Cultivars included in this study within romaine (Parris Island, Jericho, and Coastal Star) and Batavian market types (Nevada and Sierra, but excluding Cherokee) emerged as top candidates to grow during the summer heat because of the higher plant weights, sugar concentrations, and lower sugar:SL ratio, as well as decreased SL concentrations. Overall, SL and sugar concentrations were notably low in the Winter 2021 harvest season for all cultivars and market types. Growers can optimize their production and ensure better plant yield and quality by strategically choosing lettuce market types and cultivars that have better plant growth and predicted flavor for different seasons in a greenhouse.